六例母细胞性浆细胞样树突细胞肿瘤患者的临床特征 (Zhonghua Xue Ye Xue Za Zhi, 2017)
OBJECTIVE: To explore the clinical characteristics, treatment, and prognosis of patients with blastic plasmacytoid dendritic cell neoplasm. METHODS: Clinical records of 6 patients diagnosed with blastic plasmacytoid dendritic cell neoplasm in our hospital from January 2008 to May 2016 were collected and retrospectively analyzed. RESULTS: Six patients manifested with initial symptoms of skin lesions, other common symptoms included bone marrow involvement (5/6), lymphadenectasis (4/6), splenomegaly (4/6), and hepatomegaly (3/6). In addition, extra-nodal involvement except skin was also observed, including breast (1/6), maxillary sinus (1/6), vertebrae (1/6), and central nervous system (1/6). Characteristic immunophenotype, CD4, CD56, and CD123 were all positive. All these patients were treated with acute lymphoblastic leukemia type (ALL-type) chemotherapy and complete remission (CR) were reached in 4 patients. The median follow-up was 9.5 (7–37) months, median progression free survival was 7 months; while median overall survival was 9 months. A total of 3 patients died during the follow-up, which were all happened in the first year after diagnosis, and all resulted from the relapse or disease progression. CONCLUSION: Blastic plasmacytoid dendritic cell neoplasm is highly aggressive, in which the skin lesions are always manifested as initial symptoms, and bone marrow involvement, lymphadenectasis, splenomegaly, and hepatomegaly is also common. Characteristic immunophenotype include the positivity of CD4, CD56, and CD123. Effective and standard therapy is limited in this disease, which indicates the poor prognosis.